Assessment of Gelatin-Chitosan Interactions in Films by a Chemometrics Approach - Lopez-Angulo, D (Taylor and Francis Ltd., 2015)
Information looking at the interaction mechanism of chitosan-gelatin is scarce. The objective of this work was to analyze the interactions between chitosan and bovine (BG) and salmon gelatins using a chemometrics approach based on the multivariate statistical analysis, partial least square regression (PLSR), with data collected from amino acid profiling and differential scanning calorimetry.Gelatins showed differences in imino acid profile (higher amount of proline and hydroxyproline in BG). Chitosan modified the microstructure of films as indicated by variations in glass transition temperature (Tg), heat capacity (Cp), melting temperature (Tm), and enthalpy (H), in partially crystalline and amorphous films due to the effect of chitosan on gelatin chain renaturation and moisture content. PLSR showed that thermal properties of gelatin-chitosan films were affected by presence of amino acids Cysteine, Tyrosine, Valine, Arginine, Hydroxyproline, and Glycine, which would modify the orientation of side chains of polymer, while charged amino acids would encourage gelatin renaturation rather than gelatin-chitosan interaction. © 2014 Taylor and Francis.